Pengaruh Risiko Bank adn Fundamental Makroekonomi terhadap Nilai Perusahaan dengan Variabel Moderasi Profitabilitas pada Perusahaan Perbankan di Indonesia - Basri, Michelle; Thamrin, Kemas Muhammad Husni; Andriana, Isni (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of bank risk by using indicators of Non Peforming Loan (NPL), “Operating Expenses Operating Income (BOPO), and Loan to Deposit Ratio (LDR) as well as the effect of macroeconomic fundamentals by using indicators Exchange Rates (XCH), Interest Rate (IR), dan Gross Domestic Bruto (GDP) on firm value with indicator Price Earning Ratio (PER) with variable moderating profitability by using indicator Net Interest Margin (NIM). The number of samples used in study are 27 banking companies listed on Indonesia Stock Exchange in 2012-2021. The type of data is secondary data in the form of financial reports and analyzed by multiple linear analysis. The result show that in bank risk variables, BOPO and LDR had a negative and significant effect, while NPL had no effect on firm value. In Macroeconomic fundamentals variables, IR and GDP had negative and significant effect while XCH had positive and significant effect on firm value. NPL, LDR, IR, and GDP are moderated by NIM had no effect while BOPO and XCH had negative and significant effect on firm value.